First space encyclopedia - Bingham,Caroline (London, Dorling Kindersley Limited, 2016)
Packed full of photography, quizzes and amazing facts, this title helps children become space experts in no time. Covering everything from observatories and rockets, to the solar system and the death of stars, it takes them on a trip of the galaxy to investigate all the planets, from Earth to Mars.
Keywords: Encyclopedia